Low-Load Unilateral and Bilateral Resistance Training to Restore Lower Limb Function in the Early Rehabilitation After Total Knee Arthroplasty: A Randomized Active-Controlled Clinical Trial - Jacksteit, Robert; Stöckel, Tino; Behrens, Martin; Feldhege, Frank; Bergschmidt, Philipp; Bader, Rainer; Mittelmeier, Wolfram; Skripitz, Ralf; Mau-Moeller, Anett (Frontiers in Medicine, 2021)
Background: Continuous passive motion (CPM) is frequently used during rehabilitation following total knee arthroplasty (TKA). Low-load resistance training (LLRT) using continuous active motion (CAM) devices is a promising alternative. We compared the effectiveness of CPM with LLRT using the affected leg (CAMuni) and both legs (CAMbi) in the early postoperative rehabilitation. Hypotheses: (I) LLRT (CAMuni and CAMbi) is superior to CPM, (II) additional training of the unaffected leg (CAMbi) is more effective than unilateral training (CAMuni). Materials and Methods: Eighty-five TKA patients were randomly assigned to three groups, respectively: (i) unilateral CPM of the operated leg; (ii) unilateral CAM of the operated leg (CAMuni); (iii) bilateral alternating CAM (CAMbi). Patients were assessed one day before TKA (pre-test), one day before discharge (post-test), and three months postoperatively (follow-up). Primary outcome: active knee flexion range of motion (ROMFlex). Secondary outcomes: active knee extension ROM (ROMExt), swelling, pain, C-reactive protein, quality of life (Qol), physical activity, timed-up-and-go performance, stair-climbing performance, quadriceps muscle strength. Analyses of covariances were performed (intention-to-treat and per-protocol). Results: Hypothesis I: Primary outcome: CAMbi resulted in a higher ROMFlex of 9.0° (95%CI -18.03 to 0.04°, d=0.76) and 6.3° (95%CI -14.31 to 0.99°, d=0.61) compared to CPM at post-test and follow-up, respectively. Secondary outcomes: At post-test, C-reactive protein was lower in both CAM groups compared with CPM. Knee pain was lower in CAMuni compared to CPM. Improved ROMExt, reduced swelling, better stair-climbing and timed-up-and-go performance were observed for CAMbi compared to CPM. At follow-up, both CAM groups reported higher Qol and CAMbi showed a better timed-up-and-go performance. Hypothesis II: Primary outcome: CAMbi resulted in a higher knee ROMFlex of 6.5° (95% CI -2.16 to 15.21°, d=0.56) compared to CAMuni at post-test. Secondary outcomes: At post-test, improved ROMExt, reduced swelling, and better timed-up-and-go performance were observed in CAMbi compared to CAMuni. Conclusions: Additional LLRT of the unaffected leg (CAMbi) proved to be more effective for recovery of function than training of the affected leg only (CAMuni), which may be mediated by positive transfer effects from the unaffected to the affected limb (cross education) and/or preserved neuromuscular function of the trained, unaffected leg.